Keakuratan Metode Black Bunch Count (Bbc) dalam Estimasi Produksi Tandan Buah Segar (Tbs) pada PT Gawi Bahandep Sawit Mekar - Rizkya Ramadha Putri; Rusmianto Rusmianto; Arif Makhsun (Jurnal Ilmiah ESAI, 2020)
The BBC method used by the corporation does not show a good level of accuracy so there is still a difference (difference) in the bbc's TBS production output with the actual production results that occur (realization) during harvest. The purpose of this final task is to find out the accuracy of the BBC methods in the period January, February, March and April used by PT GBSM.  The data analysis method used in this study is comparative analysis with the analysis tool, the Paired Sample T-test. The sampling technique in this study is a Stratified Random Sampling technique with samples taken amounting to 144 samples consisting of 10 afdeling in PT GBSM Estate 2.  The results of this study stated that in January and February the BBC method was inaccurate in estimating TBS production results at PT GBSM, while in March and April the BBC method was accurate in estimating TBS production results in PT GBSM.